To save heaven and earth : rescue in the Rwandan genocide - Burnet, Jennie E. (Cornell University Press, 2023)
"This book explores the reasons some Rwandans risked their lives to rescue people targeted in the 1994 genocide in Rwanda. The volume presents stories of heroism and of the good done amidst the evil of a genocide that nearly annihilated Rwandan Tutsi and decimated those opposed to the slaughter"-- Provided by publisher.
Keywords: Rwandan Genocide, Rwanda, 1994.; Genocide -- Rwanda -- History -- 20th century.; Tutsi (African people) -- Crimes against -- Rwanda -- History -- 20th century.; Rwanda -- History -- Civil War, 1994 -- Atrocities.; Rwanda -- History -- Civil War, 1994 -- Civilian relief.; Rwanda -- Ethnic relations -- History -- 20th century.; Tutsi (Peuple d'Afrique) -- Crimes contre -- Rwanda -- Histoire -- 20e siècle.; SOCIAL SCIENCE / Anthropology / Cultural; Atrocities; Civilian war relief; Ethnic relations; Genocide; Tutsi (African people) -- Crimes against; Rwanda; Rwanda.; African history.; Genocide & ethnic cleansing.; Anthropology.; War crimes.; History.; 1900-1999; History